2008
DOI: 10.1177/1523422307310109
|View full text |Cite
|
Sign up to set email alerts
|

Creating Career-Conducive Organizations: A Primary Intervention Approach

Abstract: The problem and the solution. This article introduces the concept of career-conducive organizations and suggests ways human resource development (HRD) professionals can help to create them. A healthy psychosocial environment is proposed to be the foundation of career conduciveness. A case is made for making healthy psychosocial environments one of an organizations' primary goals and for HRD playing a significant role in achieving this goal. Methods for improving the workplace psychosocial environment are discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…This implies an environment where employees feel contented and fulfilled; also where they feel they can grow and thrive by being provided with the appropriate challenges, opportunities and career development measures and where they feel that they are contributing and adding value to the organisation by making a difference in other people's lives. The necessity of such an environment that is conducive to pursuing careers is also supported by Gilbreath (2008). Considering the high prevalence of potential to experience turnover intention, the organisation has an extremely important and unique role to play in retaining their key individuals (senior managers).…”
Section: Resultsmentioning
confidence: 99%
“…This implies an environment where employees feel contented and fulfilled; also where they feel they can grow and thrive by being provided with the appropriate challenges, opportunities and career development measures and where they feel that they are contributing and adding value to the organisation by making a difference in other people's lives. The necessity of such an environment that is conducive to pursuing careers is also supported by Gilbreath (2008). Considering the high prevalence of potential to experience turnover intention, the organisation has an extremely important and unique role to play in retaining their key individuals (senior managers).…”
Section: Resultsmentioning
confidence: 99%
“…Although there are a variety of types of P-E fit (e.g., person-organization, person-vocation, demandsabilities, person-group, self-concept-job; Gilbreath 2008;Kristof 1996), we focused on needs-supplies fit between students and universities. Needs-supplies fit, defined as the congruence between a person's needs and what the environment supplies, is regarded as the primary influence on outcomes such as attitudes and well-being (Kristof 1996).…”
Section: Research Hypothesesmentioning
confidence: 99%
“…The literature on healthy workplaces (e.g., Cooper & Williams, 1994; Gilbreath, 2008) suggest that job control, social support, a good fit between an employee and the work environment, reasonable amounts of challenge, variety, learning, recognition and meaning are some of the key characteristics of a healthy workplace. Furthermore, the psychosocial work environment affects quality of life and satisfaction not only of employees but also of their family members (Gilbreath, 2008). For example, in a study conducted by Burke (1988), work‐related stress of employees was found to affect their spouse marital satisfaction, social participation, psychosomatic symptoms and negative feelings.…”
Section: Introductionmentioning
confidence: 99%